Factors Influencing the Pore Structure and Gas-Bearing Characteristics of Shales: Insights from the Longmaxi Formation, Southern Sichuan Basin and Northern Yunnan-Guizhou Depression, China - Li Dong; Changcheng Han; M. Santosh; Yongkai Qiu; Geng Liu; Jinghui Ma; Hao He; Chenlin Hu (Geofluids)
China hosts rich shale gas resources. The Longmaxi Formation (LF) in the Sichuan Basin is one of the important regions for shale gas exploration and extraction. Here, we investigate the pore structure and factors influencing the gas-bearing characteristics of the pores in the shale reservoirs in the LF. We employed scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), gas content testing, gas saturation testing based on nuclear magnetic resonance (NMR), overburden porosity and permeability analysis, distribution of pore size, specific surface area (SSA) analysis, and geochemical analysis. Our results show that the organic matter of the shale in the LF in the study area is highly favorable to shale gas conditions; the brittleness of the regional shale generally increases with an increase in depth. The pores in the LF mainly include organic matter-hosted pores, intergranular pores, intragranular pores, and microfissures, with mesopores dominating. Meanwhile, the gas content also increases with an increase in depth. The pore structure in the study area is affected by organic matter content and mineral components, with the development of organic matter-hosted pores. The porosity and the SSA are positively correlated with the total organic carbon (TOC), whereas clay minerals have an adverse effect on the SSA of pores in the study area. Higher TOC and vitrinite reflectance (Ro) indicate higher gas content. It can be inferred that as the content of brittle minerals increases, particles break to form storage spaces as the depth increases, causing the gas content to increase. Higher SSA and total pore volume indicate higher volume of adsorbed gas. The bound water in rocks tends to reduce the content of desorbed gas. Our results suggest high potential for shale gas extraction in this region.